Kontrol Sudut Pitch Blade Sebagai Variable Kecepatan Angin Menggunakan Simulasi Matlab dengan Kendali Logika Fuzzy Mamdani - Muhammad Zainal Roisul Amin; Fina Farhana; Bambang Sri Kaloko (CV. Sekawan Siji, 2025)
Wind energy as an alternative energy to meet the increase in energy. However, in places with limited wind quality, it is necessary to install suitable wind turbines to generate optimal power. Installation of a vertical axis wind turbine Savonius can be carried out at unstable wind speeds. PID controllers work well when the wind is stable, but not when the wind speed changes drastically. Automatic adjustment of the angle value on a Savonius type vertical axis wind turbine is required to produce a constant output power of 20kW using a fuzzy logic controller (FLC). The membership of FLC is determined from the methodology of measuring wind speed at the calculated distance and statistical analysis of wind variability. In this way, it is possible to anticipate the response of the actuator to the gust of wind to the rotor. The test results showed that the smaller the wind speed that enters the turbine, the greater the angle of the blades. Conversely, the greater the wind speed that enters the turbine, the smaller the angle of the blades. The control results show that the resulting pitch angle parameter has a value ranging from 0 to 18.428 degrees, with a wind speed value interval of 0 to 5 m/s. The input wind speed value of 5 m/s by controlling the angle of 18.428 degrees aims to maintain the generated power value of 20,000 watts. The purpose of this research is to increase the output power and reduce the risk of rotor damage due to vibrations.